Mechanisms of plasma-assisted catalyzed growth of carbon nanofibres: a theoretical modeling. (20th January 2017) - Gupta, R; Sharma, S C; Sharma, R
Abstract: A theoretical model is developed to study the nucleation and catalytic growth of carbon nanofibers (CNFs) in a plasma environment. The model includes the charging of CNFs, the kinetics of the plasma species (neutrals, ions and electrons), plasma pretreatment of the catalyst film, and various processes unique to a plasma-exposed catalyst surface such as adsorption of neutrals, thermal dissociation of neutrals, ion induced dissociation, interaction between neutral species, stress exerted by the growing graphene layers and the growth of CNFs. Numerical calculations are carried out for typical glow discharge plasma parameters. It is found that the growth rate of CNFs decreases with the catalyst nanoparticle size. In addition, the effect of hydrogen on the catalyst nanoparticle size, CNF tip diameter, CNF growth rate, and the tilt angle of the graphene layers to the fiber axis are investigated. Moreover, it is also found that the length of CNFs increases with hydrocarbon number density. Our theoretical findings are in good agreement with experimental observations and can be extended to enhance the field emission characteristics of CNFs.